Photovoltaic characterizations of nanocomposited MEH-PPV: TiO₂ organic solar cell / Fazlinashatul Suhaidah Zahid - Zahid, Fazlinashatul Suhaidah (2014)
Recently, interest has been growing in these past few years in incorporating poly [2- methoxy-5-(2-ethyl-hexyloxy)-l,4-phenylene-vinylene] (MEH-PPV) polymer and Titanium Dioxide (TiO₂) nanocomposite based organic solar cell devices. The MEHPPV: TiO₂ nanocomposite was being studied more closely because it is possible to combine the desirable characteristics between MEH-PPV and TiO₂ within a single composite for organic solar cell application. In this study, several critical parameters were studied regarding the optimum properties of MEH-PPV: TiO₂ for use in organic solar cell including the composition of TiO₂ nanoparticles present in MEH-PPV polymer matrix (0- 40wt%), the choice of organic solvent to dissolve MEH-PPV polymer (chloroform,tetrahydrofuran, toluene, xylene and dichlorobenzene) and the influence of nanocomposite thin film’s drying temperature (50-125°C). Moreover, synthesize and modification of TiO₂ nanoparticles size to be embed in MEH-PPV polymer been studied by varied its precursor molar concentrations (0.1-0.5M) and Niobium (Nb) doping concentrations (0-10 at.%) prepared by sol-gel immerse heated method. The deposition and fabrication of MEH-PPV: TiO₂ nanocomposite based organic solar cell has been carried out by spin-coating deposition method. The properties of TiO₂ nanoparticles and MEH-PPV: TiO₂ nanocomposite thin films were analyzed using X-Ray diffraction, energy dispersive X-Ray spectroscopy, field emission scanning electron microscopy ultraviolet-near-infrared spectrophotometer, surface profiler and two-probe current-voltage measurement systems…